Effectiveness of the Blended Learning Model in Indonesian Language Learning Strategies Lectures in the Digital Era - Luluk Mukaromah; Dinda Syafa Kayla; Salsabila; Ariyana (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to determine the effectiveness of the blended learning model in increasing the learning interest of new students in the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of Tangerang. In addition, this study also examines the implementation as well as the challenges that occur in this learning model. This research uses a qualitative descriptive method. The results of the study reveal that the effectiveness of the blended learning model is measured through direct observation and the completion of questionnaires (Google Form) by new students. Challenges in online implementation include a lack of understanding of the material, unstable network connections, low participation levels, and difficulty maintaining focus. Meanwhile, challenges in face-to-face learning include students lack of self-confidence during meetings, especially because they feel uncomfortable being the center of attention when making presentations.